Mauquf’alaih as a waqf accountability center (prophetic social approach) - Siti Nurngaini; Mahfud Sholihin (Journal of Islamic Accounting and Finance Research, 2023)
Purpose - This study aims to explore Kuntowijoyo's prophetic social thinking to make mauquf ‘alaih the main focus of waqf accountability.Method - This research is a conceptual paper that attempts to construct the concept of waqf accountability in a prophetic social approach.Result - The author's opinion emphasizes the rights of the mauquf ‘alaih by highlighting how the accountability role of waqf needs to shift emphasis from serving stakeholders hierarchically to being re-engineered towards beneficiaries (mauquf ‘alaih). This requires a reconceptualization of the meaning of waqf, which must be seen as part of a wider effort to achieve social justice and the welfare of the ummah. In this case, the prophetic social value is considered as the conceptual framework.Implication - Theoretically and contextually prophetic social principles are able to give birth to a reorientation of waqf accountability towards deeper humanist and emancipatory realizations, as well as more holistic and religious accountability practices.Originality - This research is the first study that used prophetic sosial approach in waqf accountability.